The Investigation of the Suitability and Usage Status of the Disabled Toilets Located on Hacettepe University Main Campus - Gamze Yıldırım; Hatice Abaoğlu; Hülya Kayıhan; Burcu Semin Ake (Hacettepe Üniversitesi Sağlık Bilimleri Fakültesi Dergisi, 2016)
The aim of this study was to investigate suitability, hygiene and use of the disabled toilets located on Hacettepe University. Forty-two individual from Hacettepe University Disabled Students Unit were enrolled in the study. The disabled toilets standards were evaluated by a 21 item-checklist, which was organized by the researchers based on “Universal Standards Guide for Persons with Disabilities”, published by World Disability Union in 2011. In addition, a questionnaire composed of 5 items was used for observation of the toilets in terms of hygiene. In order to analyse the usage status of the disabled toilets, a semi-structured interview form was applied to the participants. At the end of this study, it was concluded that there is a lack of disabled toilets and the disabled toilets were not totally adequate for sanitation conditions and World Disability Union standards. It was determined that 11.9% of the students who were included in the study used the disabled toilets. The reason that most students didn‟t prefer the disabled toilets was the absence of adequate number of the university- disabled toilets. In light of the findings, it is emphasized that the numbers of the toilets, which are in accordance with standards and hygiene conditions, should be increased in the universities. It can be recommended that more attention needs to be given to the mobility and access requirements of students with disabilities taking into account individual and environmental factors that affect the use of the toilets